Dampak Menonton Drama Korea Terhadap Kerohanian Wanita Kristen - Oey Amellya Agustina; Iskak Sugiyarto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The spiritual aspect of believers will be influenced by what they see. Those who watch various available shows, especially Korean dramas, are often not selective and gradually become more engrossed and immersed in various Korean drama shows. The purpose of this study is to provide an overview or concept for Christian women in the age range of 50 to 65 years regarding the impacts of watching Korean dramas on their spiritual lives and to see the Bible's perspective on this issue. This study uses a descriptive qualitative method with a hermeneutic approach to see the relevance of the interpretation of Titus 2:3-5 with the title of this journal. The results of this study are that Christian women aged 50 to 65 years will spend more time because Korean drama shows that bewitch viewers, making this group vulnerable to being infiltrated with a consumptive lifestyle or way of life because of the impact of watching shows and potentially distancing them from their social spiritual life in church. Therefore, it is necessary to limit time and be willing not to get carried away and immersed when watching various Korean drama series on several paid stations. And demand their awareness to be an example taught in the verses in Titus 2:3-5.